Pengotomasian pusat kediaman pelajar Kolej Delima / Saini Taiban ... [et al.] - Taiban, Saini; John Madod, Joseph Tiyam; Abeng, Seline; Sujal, Janilah (1990)
This project is a continuation of the proposed automation system of registration and placement of students at Delima College by the previous ADDS (M) students. In continuing the project, our group which consists of 5 members have carried out a feasibility study and have come out with some findings and recommendations. The scope of our study is confined to Delima College only. In collecting data for the project, we had done some desk research for secondary data and had also conducted personal interviews with the Warden and staff of Delima College, Officials and staff of Students Affairs Department and also some students who are residents of Delima College.